Knowledge, attitude, and acceptance regarding COVID-19 vaccines in Sudan - Hazeem A. Mohmmed; Ragda Abdalmonem Alawad; Ahmed K. Awad; Abdalaziz Awad Alobied (Frontiers Media S.A., 2022)
BackgroundCOVID-19 is a respiratory disease caused by SARS-CoV-2, a new coronavirus discovered in December 2019 in China. COVID-19 symptoms are similar to those of viral flu but may be more severe, these symptoms can be defended by vaccines, the most distributed 6 candidate vaccines are Pfizer, BioNTech, Moderna, Johnson & Johnson/Janssen AstraZeneca, Sinopharm, Sinovac. In Sudan, the virus has rapidly spread in the country, causing a total of 37,138 confirmed cases with 2,776 deaths till July 21, 2021. We are targeting health workers, medical students, and the general public to assess their behavior regarding COVID-19 vaccines in Sudan, recognize the determinants of their behavior, and identify the factors increasing vaccine acceptance among them.MethodsWe conducted a pretested cross-sectional online survey involving healthcare workers, medical students, and the general population in Sudan in July and August. We collected the data by sending the survey to social media platforms (e.g., Facebook and WhatsApp). The survey was conducted anonymously without identity-related data. We used both convenience sampling and snowball sampling methods as the participants were asked to forward the survey link to their contacts. The sample size was calculated using Slovin's formula and we estimated the sample size to be 400.ResultsOf our 400 participants, 36.8% (n = 147) were males and 63.2% (n = 253) were females, the mean age of the participants was 24.17 ± 8.07. The overall vaccine acceptance rate was 48.2% (n = 193) and "Occupation" was the only sociodemographic domain significantly associated with vaccine acceptance, showing a higher acceptance rate among health care workers (p = 0.009). "Afraid of unknown side effects" was the most commonly reported barrier to vaccination (p = 0.33).ConclusionThe vaccine acceptance rate is low, and public health authorities and the government in Sudan have a heavy mission for implementing successful vaccination programs with high coverage.